Efficacy of a novel bone preprocessing method for better DNA yield. (August 2021) - Sahoo, Subhasish; Samal, Rashmita; Biswas, Sumit
Highlights: A novel method for preprocessing of bone samples, the scrapping method has been proposed. The scrapping method has significantly higher DNA yields than the conventionally used grinding method. The STR profiles generated after the scrapping method are more complete than the ones generated after the grinding method, across different DI values. Abstract: In cases involving identification of missing persons, mass disasters and ancient DNA investigations, bone and teeth samples are often the only, and almost always the best, biological material available for DNA profiling. Standard methods for extraction of DNA from such samples involve grinding of the bone and teeth samples. Here, we present an extremely efficient protocol for recovery of DNA from bone samples by a method of scrapping. The study was carried out on 25 samples and it was found that the quantity of DNA isolated by the scrapping method was up to 1.131 ng/µl with a success rate of 93% as compared to a much lower yield of 0.359 ng/µl DNA isolated with a success rate of 28% through the grinding method. The scrapping method of DNA extraction has been proven to be extremely useful in forensic examination of challenging samples that had multiple failures using the traditional grinding method.